System Modeling of Author’s Image in Texts of One Speech Genre - N. I. Tyukaeva; K. I. Brinev (Научный диалог)
The question of the method of describing of Author’s Image in Texts in modern linguistics is discussed in the article. It is argued that this technique requires the development of principles focused on systems engineering. The authors of the article note that one of the problems of modern genre studies is that a large amount of research in this area in aggregate reflects various approaches to the description of the “image of the author” in texts of the genre. The novelty of the research is seen in the fact that for an objective description of the author’s image, the hypothesis of “Functional modeling of the author of the genre” is put forward: the model of the genre system in the epistemological description has a complex level structure. The authors of the article put forward their own development of the technology for describing the image of the author of the genre, defining this technology as effective and consistent with the principles of a systematic approach to genre phenomena. In order to solve the problem of the attributive aspect of describing a genre, that is, to determine its units, it seems productive to analyze the genre according to the so-called communicative-semiotic model. The article proposes ways of solving emerging problems concerning the principles of objectivist description of the author’s model of the genre.